New evidence of factor structure and measurement invariance of the SDQ across five European nations - Ortuño-Sierra, Javier; Fonseca-Pedrero, Eduardo; Aritio-Solana, Rebeca; Velasco, Alvaro Moreno; de Luis, Edurne Chocarro; Schumann, Gunter; Cattrell, Anna; Flor, Herta; Nees, Frauke; Banaschewski, Tobias; Bokde, Arun; Whelan, Rob; et al. (Springer, 2015)
The main purpose of the present study was to test the internal structure and to study the measurement invariance of the Strength and Difficulties Questionnaire (SDQ), self-reported version, in five European countries. The sample consisted of 3012 adolescents aged between 12 and 17 years (M = 14.20; SD = 0.83). The five-factor model (with correlated errors added), and the five-factor model (with correlated errors added) with the reverse-worded items allowed to cross-load on the Prosocial subscale, displayed adequate goodness of-fit indices. Multi-group confirmatory factor analysis showed that the five-factor model had partial strong measurement invariance by countries. A total of 11 of the 25 items were non-invariant across samples. The level of internal consistency of the Total difficulties scores was .84, ranging between .69 and .78 for the SDQ subscales. The findings indicate that the SDQ's scales need to be modified in various ways for screening emotional and behavioural problems in the five European countries that were analyzed.